Interplay of EMT and CSC in Cancer and the Potential Therapeutic Strategies - Tanabe, Shihori; Quader, Sabina; Cabral, Horacio; Ono, Ryuichi (Frontiers in Pharmacology, 2020)
The mechanism of epithelial-mesenchymal transition (EMT) consists of cellular phenotypic transition from epithelial to mesenchymal status. The cells exhibiting EMT exist in cancer stem cell (CSC) population, which is involved in drug resistance. CSCs demonstrating EMT feature remain after cancer treatment, which leads to drug resistance, recurrence, metastasis and malignancy of cancer. In this context, the recent advance of nanotechnology in the medical application has ascended the possibility to target CSCs using nanomedicines. In this review article, we focused on the mechanism of CSCs and EMT, especially into the signaling pathways in EMT, regulation of EMT and CSCs by microRNAs and nanomedicine-based approach to target CSCs.